Simulation with system dynamics on university student research - Laberiano Andrade-Arenas; David Llulluy Nuñez; Alexi Delgado (Institute of Advanced Engineering and Science, 2022)
Currently, student research at the university under study is carried out from the first semesters until the student graduates, but it is necessary to make adjustments to its guidelines that include student research within a teaching-learning process. The objective of the research is to propose a model of student research, using causal diagrams and forrester diagram; then carry out a simulation of the projection from 2021 to 2026 with the variables, students, quality teachers in the research, completed work for publication in journal or conference; and thus index in Scopus or Web of Science. Besides, in the methodological part, the systems dynamics method was applied, based on the systemic approach. The research work is predictive, which was carried out with the Vensim software, obtaining as a result of the simulation, an increase in the production of complete Works by the students; where in 2026 around 300 articles will be published by the students. In addition, there will be about 12 full-time quality research professors and approximately 6,000 students in 2026. The conclusion reached in the research is that the model helps the authorities make decisions appropriately according to the forecasts made in the different scenarios made with the Vensim software.